Lessons learned developing and piloting interprofessional handover simulations for paramedic, nursing, and physiotherapy students. Issue 1 (2nd January 2017) - Stow, Jill; Morphet, Julia; Griffiths, Debra; Huggins, Chris; Morgan, Prue
ABSTRACT: Interprofessional education is an important element in the preparation of healthcare students who can communicate effectively and work collaboratively. A grant from Health Workforce Australia funded a shared nursing, paramedicine, and physiotherapy simulation suite and a staff member dedicated to interprofessional simulation, with the aim of increasing high fidelity simulation within and across the three professions. This article describes the development process and pilot testing of four purpose-designed interprofessional handover scenarios for paramedic, nursing, and physiotherapy students. The scenarios tracked an elderly patient (manikin) with a fractured neck of femur from pre-hospital to postoperative assessment and handover. The National League of Nursing Simulation Design Scale was used to evaluate the scenarios. Students' feedback indicated they considered the simulations to be relevant to their practice, with a high level of fidelity. This study re-emphasises the importance of pilot testing simulations before use in large-scale studies.